Kualitas Kayu Lapis dari Finir Bagian Juvenil dan Dewasa Samama (The Quality of Plywood Made from Juvenile and Mature Wood Veneer of Samama - Tekat D Cahyono; Imam Wahyudi; Trisna Priadi; Fauzi Febrianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2017)
This study designed 7 types of plywood that were arranged by juvenile and mature part of samama (Anthocephalus macrophyllus) wood, The adhesive used was urea formaldehyde with addition of hardener (NH4Cl) in ratio of 100:1 (weight/weight). The adhesive was applied on both surfaces of core veneer, which were loose and tight surfaces, with glue spread was 150 g m-2. The veneers were arranged in accordance with the research design and the resulted structures were then hot pressed at 110 C for 30 seconds per mm of the plywood’s thickness. The pressure was 10 kg cm-2. The results showed that bonding strength of plywood made from juvenile samama veneer was lower than that of the mature one, although the value was still met SNI standard for type I interior plywood. Furthermore, plywood’s moisture content was also met the requirement of the standard. Plywood density was increased by 11-12% from that of the wood. These findings suggest the suitability of both juvenile and mature wood of samama for the material of good quality plywood. Further studies on determination of other veneer-based products, such as laminated veneer lumber (LVL), were then recommended.Keywords: juvenile, mature, plywood, samama, urea formaldehyde